2010
DOI: 10.1080/00140139.2010.535020
|View full text |Cite
|
Sign up to set email alerts
|

The between-day and inter-rater reliability of a novel wireless system to analyse lumbar spine posture

Abstract: Peter(2011) 'The between-day and inter-rater reliability of a novel wireless system to analyse lumbar spine posture ', Ergonomics, 54: 1,[82][83][84][85][86][87][88][89][90] To link to this Article: DOI: 10.1080/00140139.2010.535020 URL: http://dx.doi.org/10.1080/00140139.2010.535020Full terms and conditions of use: http://www.informaworld.com/terms-and-conditions-of-access.pdf This article may be used for research, teaching and private study purposes. Any substantial or systematic reproduction, re-distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 64 publications
(90 reference statements)
2
19
0
Order By: Relevance
“…Sheeran et al (2010) assessed between-day measurement error for the spine wheel device and found errors ranging from 4.08to 7.48. O'Sullivan et al (2011) found the SEM for between-day reliability for the Body-Guard monitor device to be 4.08. Since that device monitored specific lumbar segment movements, it is expected such instrument will have a lower SEM than the Spineangel w , which monitors gross trunk movement.…”
Section: Between-day Reliability For Spineangel W Measurementsmentioning
confidence: 96%
See 2 more Smart Citations
“…Sheeran et al (2010) assessed between-day measurement error for the spine wheel device and found errors ranging from 4.08to 7.48. O'Sullivan et al (2011) found the SEM for between-day reliability for the Body-Guard monitor device to be 4.08. Since that device monitored specific lumbar segment movements, it is expected such instrument will have a lower SEM than the Spineangel w , which monitors gross trunk movement.…”
Section: Between-day Reliability For Spineangel W Measurementsmentioning
confidence: 96%
“…Various methods for assessing posture have been reported in the literature (Allread, Marras, and Burr 2000;David 2005;Freitag et al 2007;Wong and Wong 2008;Teschke et al 2009;Sheeran et al 2010;O'Sullivan et al 2011;Xu et al 2011). Visual assessment is commonly used in clinical practice and for work-risk assessment, while more robust and complex methods such as the use of real-time motion capture systems are used for laboratory studies (Intolo et al 2010;Straker et al 2010).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…BodyGuard TM was validated against a traditional flexible electrogoniometer (O'Sullivan et al, 2011) and correlation was found to be high in both sitting (r=0.98) and standing (r=0.99). Excellent association for between-day (ICC≥0.84) and inter-rater reliability (ICC≥0.91) was found and reliability was evaluated as good as, or better than the other devices (O'Sullivan et al, 2011). Lumbo-pelvic posture during functional tasks and postures (sitting and standing) was measured using BodyGuard TM and a traditional laboratorybased motion analysis system and the results compared .…”
Section: Lumbar Posturementioning
confidence: 99%
“…These kinds of garments tend to be skin-tight because they rely on the body deforming or straining the sensors in the fabric during movements, which may affect social and physical comfort. One effort to increase physical comfort is via use of plastic optical fiber sensors (e.g., [21]; also see [22], for a review of further fiber optic sensors as well as many other devices for measuring spinal posture).…”
Section: Introductionmentioning
confidence: 99%